Induction of a cross-reactive idiotype dextran-positive antibody response in two IgH-Cb mouse strains treated with anti-J558 cross- reactive idiotype antibodies (The Rockefeller University Press, 1983)
The effect of IdX-specific rabbit and allogeneic antiidiotype antibodies (Ab2) was investigated in vivo in Igh-Cb mouse strains with respect to the induction of a cross-reactive idiotype (IdX)-positive anti-alpha (1-3) Dextran (Dex) response. These C.B20 and C57Bl/6 mice have an allotype-linked incapacity to respond with IdX-positive anti- alpha (1-3) Dex antibodies upon conventional immunization with Dex B1355. 7 d after the rabbit Ab2 injections, IdX-positive Ig (Ab3) and IdX-positive anti-alpha (1-3) Dex antibodies (Ab1') were detected in the sera of each tested mouse. The affinity-purified Ab1' were idiotypically indistinguishable from reference BALB/c IdX-positive myeloma proteins and BALB/c anti-alpha (1-3) Dex antibodies (Ab1) in a competitive inhibition radioimmunoassay, while Ab3 Ig appeared idiotypically deficient and did not bind to Dex. The response to the alpha (1-6) linkage of Dex was not affected in these mice. A large fraction of the Ab1' and Ab3 responses of both mouse strains were of the IgG1 class. The Ab1' antibodies differed from BALB/c Ab1 by lower relative binding to five of eight tested Dex, and by expressing the Igh4b allotype determinants on the IgG1 antibodies. This study identifies the products of a VHDex gene that appears to be under regulatory control in the Ighb mice. Its association with the b haplotype suggests that this gene may differ structurally from the BALB/c VHDex gene.